PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS THINK TALK WRITE (TTW) PADA MATERI HIDROKARBON UNTUK KELAS XI IPA MA AL-MUSTAQIM - Azimah Amalia; Fitriani Fitriani; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2019)
The development research is initiated by the lack of students’ knowledge in determining the understand the concept of hydrocarbons, and aimed at designing the student worksheet based on Think Talk Write (TTW). Using Research and Development model of 3D (Define, Design, and Develop), this study included validation sheet, teacher and students questionnaires, and pretest posttest as the instruments. The study revealed a number of findings. First, the average score of validation criteria was 94,60% (strongly valid), with an average score of media expert by 93,75% (strongly valid). Second, the results of practicality criteria taken from the students respon were 93,8% (strongly practical), and from the teacher respon was 82,8% (strongly practical). Third, the effectiveness criteria of pretest and posttest after taught using student worksheet based on TTW and counted by N-gain was considered very good (0,75). In conclusion, the student worksheet based on TTW is effectively used as teaching materials in hydrocarbon in class XI Science MA Al-Mustaqim.